Faktor yang Memengaruhi Mutu Pelayanan Medik di RSUD Pidie Jaya - Rizki Kamalia; Arifah Devi Fitriani; Mappeaty Nyorong (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Health services are one's expectations of the quality obtained in accordance with the desired expectations, such as health services, there are services in hospitals that include customers, such as patients for treatment from doctors in hospitals where patients get the best service from the hospital. The aim of the study was to determine the factors that influence the quality of service at the Pidie Jaya Hospital, Pidie Jaya Regency. The research design uses a quantitative method which is carried out by an analytical survey with a Cross Sectional Study approach. The population in this study were all outpatients with a total of 6,685 patients. The sample used random sampling technique as many as 99 patients. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an effect of technical competence p = 0.000, efficiency p = 0.000, effectiveness p = 0.000, satisfaction p = 0.000 and patient safety p = 0.000 on the quality of service in Pidie Jaya Hospital, Pidie Jaya Regency. While the most dominant factor is satisfaction p = 0.000 and 95% CI = 5,389-316,539 with OR = 41,154.The conclusion from this study is that there is an influence of technical competency, efficiency, effectiveness, satisfaction, and patient safety on service quality in Pidie Jaya Hospital, Pidie Jaya Regency. It is recommended for the hospital to adopt policies in order to improve the quality of hospital services in order to produce optimal performance such as conducting training for health workers in hospitals based on their competence and conducting supervision and monitoring so that implementation in the field can run optimally.